International Olympic Committee (IOC) consensus paper on sports-related ophthalmology issues in elite sports - Moe, M. C.; Özmert, E.; Baudouin, C.; Binadra, A.; Crafoord, S.; Jo, Y.; Kiratli, H.; Moore, M.; Pitsiladis, Y. P.; Rolle, U.; Tan, B.; Yanik, Ö.; et al. (BMJ Open Sport & Exercise Medicine, 2022)
Vision plays an important role in an athletes` success. In sports, nearly 80% of perceptual input is visual, and eye health and sports medicine are closely intertwined fields of utmost importance to athletes. The physical nature of sports activities renders individuals more prone to various eye injuries than the general population. Ocular trauma can lead to lifelong sequelae, and impaired vision requires careful follow-up and management. Apart from injuries, athletes may also experience vision problems that can hamper their performance, including blurred vision, double vision, and light sensitivity.